2016
DOI: 10.1590/0103-8478cr20150696
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and sorption of fipronil and atrazine in Latossols with organic residues from sugarcane crop

Abstract: Organic residues from sugarcane crop and processing (vinasse, boiler ash, cake filter, and straw)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…However, a greater half-life than that calculated for the cultivated bare soil (Microcosms 1 and 4) was expected due to the lack of efficient degrading microorganisms in the native soil and also due to the physical barrier offered by the straw. The half-lives obtained in the present study for the faster degradation phase are in the same order of magnitude as the values obtained in other Brazilian Oxisols that varied between 4 and 51 days Silva et al, 2016). Figures 2A and B show the water-extractable and ASE-extractable 14 C residues and results, respectively, obtained in Microcosms 1 and 2.…”
Section: Atz Mineralizationsupporting
confidence: 85%
See 2 more Smart Citations
“…However, a greater half-life than that calculated for the cultivated bare soil (Microcosms 1 and 4) was expected due to the lack of efficient degrading microorganisms in the native soil and also due to the physical barrier offered by the straw. The half-lives obtained in the present study for the faster degradation phase are in the same order of magnitude as the values obtained in other Brazilian Oxisols that varied between 4 and 51 days Silva et al, 2016). Figures 2A and B show the water-extractable and ASE-extractable 14 C residues and results, respectively, obtained in Microcosms 1 and 2.…”
Section: Atz Mineralizationsupporting
confidence: 85%
“…In the same study, a different pattern with a clayey Xanthic Haplustox from northeastern Brazil was observed, where, in addition to a lag phase of about 7 days, approximately 74 % of the initially applied 14 C-ATZ was mineralized by the end of the incubation period. Results from this study, together with data from other authors indicated that, in addition to the history of herbicide application (Bonfleur et al, 2010), physical and chemical properties of the soil (Dick et al, 2010), local environmental conditions, such as rainfall (Correia et al, 2007), topography (Aquino et al, 2013) and agricultural practices, such as straw cover (Amadori et al, 2016) and the addition of organic residues (Silva et al, 2016) may also affect the extent of ATZ dissipation.…”
Section: Accelerated Solvent Extractionsupporting
confidence: 56%
See 1 more Smart Citation
“…23 In studies on soil with a history of fipronil application, a half-life ranging from 15 to 105 days has been reported, this number varying as a result of the type of the soil being analyzed. 24 Silva et al reported that clay soils (dystroferric red latossol) have greater degradation capacity than common texture soils (dystrophic red latossol), showing a shorter half-life of 15-79 days. 24 Wolfand et al demonstrated that the persistence of fipronil in the soil is linked to the availability of oxygen that may or may not interfere in the process of degradation by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…24 Silva et al reported that clay soils (dystroferric red latossol) have greater degradation capacity than common texture soils (dystrophic red latossol), showing a shorter half-life of 15-79 days. 24 Wolfand et al demonstrated that the persistence of fipronil in the soil is linked to the availability of oxygen that may or may not interfere in the process of degradation by microorganisms. 25 Therefore, treatments performed under anaerobic and aerobic conditions took 20 and 200 days, respectively, to reach half-life.…”
Section: Introductionmentioning
confidence: 99%